Significant Progress in CAR T-Cell Therapy for Difficult-to-Treat Hematologic Malignancies - Raphaël Stadelmann; Anne Cairoli; Caroline Arber (healthbook TIMES. Oncology Hematology, 2022)
The latest clinical and real-world evidence of chimeric antigen receptor (CAR) T-cell therapy continues to challenge standard treatment paradigms for many hematologic malignancies with limited treatment options. In particular, recently approved CAR T-cell therapies are forging a path towards improving patient outcomes and health-related quality of life (HRQoL) in difficult-to-treat relapsed/refractory (R/R) blood cancers such as diffuse large B-cell lymphoma (DLBCL), multiple myeloma (MM), mantle cell lymphoma (MCL) and B-cell acute lymphoblastic leukemia (B-ALL). Here the latest data on commercially available CAR T-cell therapies are summarized and discussed.